Expression of nuclear factor erythroid 2-related factor 2 following traumatic brain injury in the human brain. Issue 5 (20th March 2019) - He, Yuxin; Yan, Huiying; Ni, Hongbin; Liang, Weibang; Jin, Wei
Abstract : Secondary brain injury imposes great effects on the prognosis of patients following traumatic brain injury (TBI). Accumulating evidence suggests that nuclear factor erythroid 2-related factor 2 (Nrf2) could play a neuroprotective role in experimental TBI models by regulating the expression of numerous antioxidant, anti-inflammatory, and neuroprotective proteins. However, whether Nrf2 is activated in patients following TBI is still unknown. In this study, human brain tissues were obtained during surgery from patients suffering from TBI. The purpose of this study was to investigate the expression of Nrf2 and Nrf2-regulated gene products, NAD(P)H quinine oxidoreductase 1, and glutathione S -transferase in human injured brain tissue after TBI. Our results revealed that the nuclear level of Nrf2 was significantly increased in injured brain tissues, whereas the cytoplasmic level of Nrf2 was markedly decreased. In addition, the expression of NAD(P)H quinine oxidoreductase 1 and glutathione S -transferase was significantly upregulated. Nrf2 may be activated and confer neuroprotection against secondary brain injury following TBI. Therefore, Nrf2 could serve as a promising molecular target for the treatment of TBI.